Darwin Koenig letter to Thomas H. Kent regarding bird sightings, July 30, 1980 - Koenig, Darwinet al (1980)
Field notes contributed by Darwin Koenig in a letter to Thomas H. Kent, July 30, 1980. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of summer 1980. Epson - sheet feed/flatbed